Research Anthology on Doctoral Student Professional Development 2022
DOI: 10.4018/978-1-6684-5602-6.ch025
|View full text |Cite
|
Sign up to set email alerts
|

Researcher Positionality in the Dissertation in Practice

Abstract: This chapter explores first the role of researcher perspective in the research process, then the unique nuances of the researcher positionality in dissertations in practice, followed by a discussion of the advantages and limitations of the unique positionality assumed by dissertations in practice. This chapter concludes by noting the importance of constructing conceptual coherence between the implications of the scholarly-practitioner's positionality statement and the discussion of the dissertation's ethical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This can be a result of the beliefs of Pearce (2002) and Sartor and Young Brown (2004), who claimed that consensus possesses the requisite model and serves as an avenue for producing critical-thinking citizens. This assertion was also corroborated by Smith (2003) and Smith and Dirkx (2007), who concluded that consensus made students learn more about content than they would have learned individually, as it broadened their horizons to look at issues from different perspectives. The cooperative reflective journal writing instructional strategy was also found to improve students' achievement in biology compared with the conventional strategy.…”
Section: Discussionmentioning
confidence: 72%
“…This can be a result of the beliefs of Pearce (2002) and Sartor and Young Brown (2004), who claimed that consensus possesses the requisite model and serves as an avenue for producing critical-thinking citizens. This assertion was also corroborated by Smith (2003) and Smith and Dirkx (2007), who concluded that consensus made students learn more about content than they would have learned individually, as it broadened their horizons to look at issues from different perspectives. The cooperative reflective journal writing instructional strategy was also found to improve students' achievement in biology compared with the conventional strategy.…”
Section: Discussionmentioning
confidence: 72%
“…Shaw (2013) assessed the qualitative perspectives of students who engaged in the Reading Education Assistance Dog (READ) program, finding higher reported confidence and comfort during their READ sessions. Smith (2009) evaluated the SitStayRead program (an 8‐week intervention program consisting of one‐hour sessions per week) and found a 20% increase in ORF scores for students who read to the dog compared with the teacher. Levinson et al (2017) evaluated the effect of reading aloud to a therapy dog and handler following five 30‐min sessions on children's ORF using a post‐test only control group design.…”
Section: Canine‐assisted Reading Programmentioning
confidence: 99%
“…To better understand children's lexical development, researchers have collected words produced by young children for word lists. Smith (1926) generated a word list for 88 children aged from 2 to 5 years based on 1-hr language samples of each child during their play with other children. Words which occurred more than 100 times across the collected conversation samples were included in the list.…”
Section: Lexical Development Before School Agementioning
confidence: 99%
“…In this study, the mean of verb tokens for 3-year-olds was 122.28, and for 4-year-olds, 152.48. Smith (1926) studied POS percentage in the 1-hr conversation of 101 English-speaking children. The results showed that there were no significant differences from year to year of any POS category; however, there might be a tendency of a greater use of adjectives and pronouns as age increases.…”
Section: Differences Between Pos Used By Different Age Groupsmentioning
confidence: 99%